Acute Angle-closure Glaucoma as a First Presentation of Coats' Disease: A Case Report. Issue 2 (February 2018) - Amro, Mazen; Haydar, Ali A.; El-Khoury, Sylvain; Tomey, Karim F.; Cherfan, George; Khoueir, Ziad
Abstract : Purpose: The purpose of this study was to report an unusual first manifestation of Coats' disease presenting as an acute angle-closure glaucoma attack in an adult patient. Patients and Methods: A 37-year-old African woman presented to the emergency department with severe headache, ocular pain, and no light perception in the left eye. The left pupil was middilated and nonreactive, and the intraocular pressure (IOP) by applanation tonometry was 47 mm Hg. Slit-lamp examination revealed anterior subcapsular opacification (glaukomflecken), posterior synechiae, and total angle closure with iris bombé. A fundus examination revealed macular exudation, inferior vascular dilation, and tortuosity with peripheral telangiectasia and macroaneurysms, in addition to partial exudative retinal detachment involving the macula. On the basis of these findings, Coats' disease was diagnosed. Results: The patient was treated with antiglaucoma medications and laser peripheral iridotomy to control the IOP, which had decreased to 21 mm Hg the following day. Diode laser transscleral cyclophotocoagulation was performed to further decrease the IOP. After completing a 360 degree laser, the IOP decreased to 8 mm Hg and then stabilized around 12 mm Hg. The vision remained no light perception; however, the patient felt major symptomatic relief. Conclusions: The present case describes acute angle-closure glaucoma as an initial presentation of Coats' disease in adults. Clinicians should be aware that this unique presentation in Coats' disease can occur even without retinal detachment.